‘Old food, new methods’: recent developments in lipid analysis for ancient foodstuffs - Vykukal, Rachel; Gabiger, Anastasia; Cramp, Lucy J.E.; Hammann, Simon (Trac-Trends in Analytical Chemistry, 2024)
In the study of ancient diet, lipid analysis of archaeological pottery residues has become a major investigative tool. Lipids absorb readily into clay vessels during cooking or processing of foodstuffs and are preserved, although not completely unchanged, for millennia. These can be linked directly to plant and animal resources used by past societies and can be valuable for understanding culinary practices, diet, and foodways. Identifying ‘old food’ via organic residue analysis has steadily developed since its inception last century, but growth has intensified in the past several years in many areas from modern reference comparisons to data interpretation. This paper will discuss current developments in the field of dietary studies using archaeological lipid analysis. Advancements in extraction methods, instrumentation, experimental ground-truthing, data processing, and interpretive frameworks are significantly boosting the explanatory power of lipid analysis for reconstructing ancient foodways and amplifying the importance of biomolecular-level data even further.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Ancient diet; Archaeology; Cooking; Gas chromatography; Lipids; Liquid chromatography; Mass spectrometry; Organic residue analysis; Pottery